2021
DOI: 10.1007/s10461-021-03289-7
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Access to HIV Services and Risky Sexual Behaviors Among Malawian Women at Social Venues Who Do and Do Not Engage in Sex Work

Abstract: In the high HIV-burden country of Malawi, female sex workers (FSW) are one of the populations most profoundly affected by HIV. The Malawi Priorities for Local AIDS Control Efforts (PLACE) surveyed 1,004 self-identified FSW, 213 other FSW (OFSW), and 130 other high risk women (OHRW) at social venues. Analyses compared the three groups using surveyweighted log binomial regression models. Each group had a distinct pattern of usage and access to services: OFSW and FSW had greater access to condoms, while using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Several studies have evaluated the efficacy of HIV risk reduction intervention efforts among WESW in SSA. For example, studies have documented consistent increases in self-reported condom use among WESW with paying partners due to improved self-efficacy in condom negotiations skills [12,13] Effective strategies included condom promotion using peer educators, condom distribution and risk reduction, distribution of education materials, and counseling sessions on HIV testing and risk reduction with program staff [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evaluated the efficacy of HIV risk reduction intervention efforts among WESW in SSA. For example, studies have documented consistent increases in self-reported condom use among WESW with paying partners due to improved self-efficacy in condom negotiations skills [12,13] Effective strategies included condom promotion using peer educators, condom distribution and risk reduction, distribution of education materials, and counseling sessions on HIV testing and risk reduction with program staff [13,14].…”
Section: Introductionmentioning
confidence: 99%